Design study of a PET detector with 0.5 mm crystal pitch for high-resolution preclinical imaging. (1st July 2021) - Zhang, Xi; Yu, Hongsen; Xie, Qiangqiang; Xie, Siwei; Ye, Baihezi; Guo, Minghao; Zhao, Zhixiang; Huang, Qiu; Xu, Jianfeng; Peng, Qiyu
Abstract: Preclinical positron emission tomography (PET) is a sensitive and quantitative molecule imaging modality widely used in characterizing the biological processes and diseases in small animals. The purpose of this study is to investigate the methods to optimize a PET detector for high-resolution preclinical imaging. The PET detector proposed in this study consists of a 28 × 28 array of LYSO crystals 0.5 × 0.5 × 6.25 mm 3 in size, a wedged lightguide, and a 6 × 6 array of SiPMs 3 × 3 mm 2 in size. The simulation results showed that the most uniform flood map was achieved when the thickness of the lightguide was 2.35 mm. The quality of the flood map was significantly improved by suppressing the electronics noises using the simple threshold method with a best threshold. The peak-to-valley ratio of flood map improved 25.4% when the algorithm of ICS rejection was applied. An energy resolution (12.96% ± 1.03%) was measured on the prototype scanner constructed with 12 proposed detectors. Lastly, a prototype preclinic PET imager was constructed with 12 optimized detectors. The point source experiment was performed and an excellent spatial resolution (axial: 0.56 mm, tangential: 0.46 mm, radial: 0.42 mm) was achieved with the proposed high-performance PET detectors.